Strength and Fracture Behaviour of Dual Phase Steel Dp450 in Static and Dynamic Conditions - Sunil Kumar Meluru Ramesha; Eva Schmidova (Communications - Scientific letters of the University of Zilina, 2019)
In this work, strength and plastic deformation effect of the dual phase steel are analysed in the static and dynamic conditions. Since the dual phase steel is extensively used in the outer body parts of the automotive vehicles, its dynamic strength and plastic strain energy absorption during the crash are essential. Dynamic strength of the dual phase steel is examined using the pendulum impact hammer tester machine. Spread of the plastic strain during the crash is an important factor for the energy absorption to passive safety, which is examined using the local hardness measurement using the Vickers hardness and local indentation yield strength is calculated using cylindrical indenter and obtained force-depth results are analysed using the Hencky theory for the plane strain indentation. Further, tested samples are observed using scanning electron microscopy for the fracture response after the static and dynamic tests.